HISTORICAL AND LEGAL FUNDAMENTALS OF THE CUSTOMARY LAW OF THE MORDVINS IN THE TRADITIONAL JURISPRUDENCE OF RUSSIA - Sushkova, Iuiia (Revista Inclusiones, 2020)
The relevance of the study is determined by the role of traditional jurisprudence as an ancient system of ethnic normative regulation. This regulation is existing in part even today in the modern world-view, the legal consciousness of the peoples of Russia. The historico-legal heritage of the peoples of the Russian Federation is a unique source of traditional jurisprudence. It accumulates various norms of their traditional legal culture, legal world-view. In this regard, the study of traditional legal culture is aimed at understanding the ancient legal traditions of specific ethnoses, their legal consciousness, possibilities of using the accumulated experience in law-creative process and resolving disputable situations. This article discloses the historico-legal foundations of the customary law of the Mordovian people. The leading method for studying the problem is the methods of field ethnography, case studies, which enable scholars to consider comprehensively the customary legal norms in various ways of their application. The sources of the study were the data from interviews of old residents of Mordovian villages, as well as documentary publications of the researchers. The article analyzes the features of the communal organization, the formation and development of customary law in the spheres of marriage-family and civil law relations. The materials of the article are of practical value for the improvement of legislation in the conditions of a multinational state, which is the Russian Federation. The knowledge on customary law helps to increase ethnic tolerance and to form goodneighborly relations between people.